Histone acetylation: a switch between repressive and permissive chromatin: Second in review series on chromatin dynamics - Eberharter, Anton (Oxford University Press, 2002)
The organization of eukaryotic chromatin has a major impact on all nuclear processes involving DNA substrates. Gene expression is affected by the positioning of individual nucleosomes relative to regulatory sequence elements, by the folding of the nucleosomal fiber into higher-order structures and by the compartmentalization of functional domains within the nucleus. Because site-specific acetylation of nucleosomal histones influences all three aspects of chromatin organization, it is central to the switch between permissive and repressive chromatin structure. The targeting of enzymes that modulate the histone acetylation status of chromatin, in synergy with the effects mediated by other chromatin remodeling factors, is central to gene regulation.